Poor Folate Intake in a North Italian Pregnant Population: an Epidemiological Survey. Issue 6 (14th September 2015) - Dante, Giulia; Morani, Letizia; Bronzetti, Daisy; Garutti, Paola; Neri, Isabella; Calapai, Gioacchino; Facchinetti, Fabio
Abstract Background The association between folic acid (FA) insufficiency and congenital malformations has been demonstrated in over the past two decades. The aim of the present study was to investigate the use and timing of folate intake among a large sample of pregnant women in a north Italian region. Methods A multicentre prospective cohort study was conducted over a 14‐month period in the maternity wards of five general hospitals (2301 women). Data were collected via a face‐to‐face interview. Results Seven hundred sixty women (33%) took at least one product containing FA. Seven hundred thirty‐three (31.8%) women consumed multivitamins containing 413 (17.9%) consumed products containing FA only and 17 (0.7%) 15 mg of levofolinic acid. Only 0.9% of all women took FA before pregnancy 72.5% of women who consumed FA started during the first trimester. The most common dosage was 0.4 mg (19.4%). Conclusions Very few women in the population are taking FA before pregnancy. Moreover, while most women consuming FA started in the first trimester, it is likely that they did so after closure of the neural tube. An important action is the recommendation that periconceptional supplementation programmes be promoted.